2020
DOI: 10.1007/s00262-020-02524-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated vimentin as an immunotherapeutic target against metastatic colorectal cancer

Abstract: Colorectal cancer (CRC) patients with metastatic lesions have low 5-year survival rates. During metastasis, cancer cells often obtain unique characteristics such as epithelial-mesenchymal transition (EMT). Vimentin a biomarker contributes to EMT by changing cell shape and motility. Since abnormal phosphorylation is a hallmark of malignancy, targeting phosphorylated vimentin is a feasible approach for the treatment of metastatic tumors while sparing non-tumor cells. Recent evidence has revealed that both CD8 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This suggests that lack of vimentin expression does not allow for its EMT function, and tumor metastasis may be promoted through other routes. Recently, some studies [ 31 35 ] have proposed vimentin as a potential molecular target for treatment of some kinds of cancers; however, our results suggest enough prudence in using it for EC.…”
Section: Discussionmentioning
confidence: 56%
“…This suggests that lack of vimentin expression does not allow for its EMT function, and tumor metastasis may be promoted through other routes. Recently, some studies [ 31 35 ] have proposed vimentin as a potential molecular target for treatment of some kinds of cancers; however, our results suggest enough prudence in using it for EC.…”
Section: Discussionmentioning
confidence: 56%
“… 72 Phosphorylation of waveform proteins promotes the growth of metastatic tumors and the high expression of waveform proteins indicates the activation of EMT in malignant tumors. Ohara et al 73 reported that a novel phosphorylated helper peptide epitope in the waveform protein could induce sufficient T cell responses, suggesting that immunotherapy targeting phosphorylated waveform proteins could be a promising treatment strategy for patients with metastatic colorectal cancer.…”
Section: Treatment and Drug Resistance Of Crc Associated With Emtmentioning
confidence: 99%
“…Interestingly, we detected TWIST1 140–162 peptide‐specific production of not only IFN‐γ but also TNFα and granzyme B in the samples from BC5, BC6, and BC7, indicating that they showed a Th1 cell phenotype (Figure 4). As we had previously demonstrated that granzyme B‐producing HTLs directly killed tumor cells, 31,32 these TWIST1‐specific HTLs would show antitumor cytotoxicity. These results suggested that the TWIST1 140–162 peptide could effectively activate TWIST1‐specific HTLs to enhance cell‐mediated immunity against tumors expressing TWIST1/2.…”
Section: Resultsmentioning
confidence: 94%